2016
DOI: 10.18203/2394-6040.ijcmph20163057
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of hypertension and its associated risk factors in a sub-urban area of central Nepal

Abstract: INTRODUCTIONNon communicable diseases (NCDs) are one of the leading causes of mortality and morbidity worldwide afflicting more in developing countries. In 2012, of the total 56 million deaths worldwide, NCD accounted for more than 50% (i.e. 38 million deaths). Of these, more than 70% (28 million deaths) of NCD deaths occurred in low and middle income countries. 1It is interesting to note that, cardiovascular diseases (CVDs) alone lead to 46.2% of NCD deaths followed by cancer, respiratory diseases and diabete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
14
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 22 publications
3
14
1
Order By: Relevance
“…Our study found comparatively high prevalence of CVD risk factors than that of the national representative estimate21, 37, 38 and the findings from a number of studies from similar settings in Nepal 16, 39, 40, 41…”
Section: Discussionsupporting
confidence: 71%
“…Our study found comparatively high prevalence of CVD risk factors than that of the national representative estimate21, 37, 38 and the findings from a number of studies from similar settings in Nepal 16, 39, 40, 41…”
Section: Discussionsupporting
confidence: 71%
“…This association was statistically significant (p value = <0.05) with an odds ratio of 1.5. Similar findings were seen in another study done by Shrestha et al 23 Metabolic factors like diabetes and obesity increase the risk of complications of hypertension like heart disease, stroke and renal failure. 8 In this study there was a statistical significant association between hypertension and BMI of more than 25 (p value = <0.05).…”
Section: Figure 1: Prevalence Of Hypertension Among the Study Populatsupporting
confidence: 90%
“…Most participants (47.4%) never added salt before or during eating food while 97.0% used to add salt while cooking foods. Only 5.8% of the participants always consumed processed food high in salt while 37.9% participants only sometimes Nepalese Heart Journal 2019; Vol 16(1), [19][20][21][22][23][24][25][26] consumed such food items.…”
Section: Resultsmentioning
confidence: 99%
“…Nepalese Heart Journal 2019; Vol 16(1), [19][20][21][22][23][24][25][26] The early systemic HTN study in Nepal was done in early eighties by Mrigendra Samjhana Medical Trust. 7 The then used World Health Organization (WHO) criteria (160/95mmHg) were used to diagnose HTN.…”
mentioning
confidence: 99%